2010
DOI: 10.1177/0960327109359460
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carnosine pretreatment on oxidative stress and hepatotoxicity in binge ethanol administered rats

Abstract: Carnosine is a dipeptide having strong antioxidant effects. Oxidative stress plays an important role in pathogenesis of alcohol-induced liver injury. In this study, we investigated the effect of carnosine pretreatment on ethanol-induced oxidative stress and hepatotoxicity. Rats were given carnosine (2 g/L in drinking water) for 4 weeks and then ethanol was administered orally to rats at a dose of 5 g/kg every 12 hours for 3 doses totally (binge model). All rats were killed 6 hours after last ethanol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
5
27
0
2
Order By: Relevance
“…Moreover, neither binge ethanol nor MAOIs had any significant effect on the protein expression of SOD2 or catalase. Several studies have reported changes in expression/activity of SOD2 and catalase following ethanol exposure, while others have not (Carmiel-Haggai et al, 2003; Artun et al, 2010; Nogales et al, 2014). However, in the brain, catalase is largely responsible for the metabolism of ethanol to acetylaldehyde (Ledesma et al, 2014), which explains why we observed a group effect in binge ethanol-treated rats for increased catalase expression compared to control rats, regardless of MAOI administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, neither binge ethanol nor MAOIs had any significant effect on the protein expression of SOD2 or catalase. Several studies have reported changes in expression/activity of SOD2 and catalase following ethanol exposure, while others have not (Carmiel-Haggai et al, 2003; Artun et al, 2010; Nogales et al, 2014). However, in the brain, catalase is largely responsible for the metabolism of ethanol to acetylaldehyde (Ledesma et al, 2014), which explains why we observed a group effect in binge ethanol-treated rats for increased catalase expression compared to control rats, regardless of MAOI administration.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of ROS is also a critical mode of ethanol-induced cellular dysfunction (Ramachandran et al, 2003; Das and Vasudevan, 2007; Gonzalez et al, 2007; Boyadjieva and Sarkar, 2013). Oxidative stress is a devastating consequence of binge drinking and, thus, antioxidants provide substantial neuroprotection in models of binge ethanol exposure (Hamelink et al, 2005; Crews et al, 2006; Artun et al, 2010; Collins and Neafsey, 2012; Nair et al, 2015). Further, oxidative exposure of proteins due to ROS can modify their characteristics and function, such as enzymatic activity, binding of transcription factors, and increasing susceptibility to proteolytic degradation (Wolff and Dean, 1986; Davies, 1987; Davies et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress plays an important role in the pathogenesis of alcohol-induced liver injury. Research in ethanol-treated rats indicates that carnosine prevents increased serum transaminase and lipid peroxide activity in the liver without any change in steatosis [18]. The protective effects of carnosine and histidine against acetaminophen-induced hepatotoxicity were shown in another study [19].…”
Section: Discussionmentioning
confidence: 99%
“…L-carnosine acts as an antioxidant by scavenging hydroxyl radicals, binding divalent metals, upregulating enzymes that metabolize free radicals, and by promoting antiglycation [23, 24]. As a result, carnosine has been used as a protective agent in stroke models [25], liver injuries [26], and ophthalmologic disorders [27]. …”
Section: Discussionmentioning
confidence: 99%